Individually dosed omalizumab: an effective treatment for severe peanut allergy. Issue 4 (10th January 2017) - Brandström, J.; Vetander, M.; Lilja, G.; Johansson, S. G. O.; Sundqvist, A.‐C.; Kalm, F.; Nilsson, C.; Nopp, A.
Summary: Background: Treatment with omalizumab has shown a positive effect on food allergies, but no dosages are established. Basophil allergen threshold sensitivity (CD‐sens) can be used to objectively measure omalizumab treatment efficacy and correlates with the outcome of double‐blind placebo‐controlled food challenge to peanut. Objective: To evaluate whether individualized omalizumab treatment monitored by CD‐sens could be an effective intervention for suppression of allergic reactions to peanut. Methods: Severely peanut allergic adolescents ( n = 23) were treated with omalizumab for 8 weeks, and CD‐sens was analysed before and after. Based on whether CD‐sens was suppressed after 8 weeks, the patients either were subject to a peanut challenge or received eight more weeks with increased dose of omalizumab, followed by peanut challenge or another 8‐week cycle of omalizumab. IgE and IgE‐antibodies to peanut and its components were analysed before treatment. Results: After individualized omalizumab treatment (8–24 weeks), all patients continued with an open peanut challenge with no ( n = 18) or mild ( n = 5) objective allergic symptoms. Patients ( n = 15) needing an elevated omalizumab dose (ED) to suppress CD‐sens had significantly higher CD‐sens values at baseline 1.49 (0.44–20.5) compared to those ( n = 8) who managed with normal dose (ND) 0.32 (0.24–5.5) ( P < 0.01). Median ratios for Ara h 2 IgE‐ab/IgE were significantly higher in the ED group (17%) compared to the ND group (11%). Conclusions and Clinical Relevance: Individually dosed omalizumab, monitored by CD‐sens, is an effective and safe treatment for severe peanut allergy. The ratio of IgE‐ab to storage protein Ara h 2/IgE as well as CD‐sens to peanut may predict the need of a higher omalizumab dose. Clinical trials numbers: EudraCT; 2012‐005625‐78, ClinicalTrials.gov; NCT02402231.